A case study in applying software certification model by product quality approach - Yahaya, J.H.; Deraman, Aziz; Hamdan, Abdul Razak (Institut Teknologi Bandung, 2007)
Recently, software quality issues have seen as important issues as we see a tremendous growth of companies and agencies involved in software industries. The questions that need to consider in this circumstances is the quality of this software and how do we determine the quality of the software based on certain perceptions and standard.Software quality assurance affects both immediate and long-term profitability of the organizations. Thus, it is critically important for the survival of companies both in private and public sectors. This paper describes a case study that used and evaluated key aspects of a method developed for software product assessment certification process. It is an end-product quality approach that considers assessment of completed software product. The proposed model consists of pragmatic quality model as the benchmark of the assessment, weighted scoring method, decision framework, repository and certification representation method. We have applied the model in two case studies which involved collaboratively with three large organizations in Malaysia, assessing two main systems developed by these organizations. The case studies indicated that the evaluated aspects of proposed model are feasible and demonstrate the potential and practicality in supporting the process of certification. The proposed model eliminates bias assessment, remove unfairness evaluation and protect data privacy and confidentiality. This paper reports one of the case studies.